ANTIOXIDANT, ANTIBACTERIAL, AND ANTICANCER ACTIVITY FROM MARINE RED ALGAE GRACILARIA EDULIS. - TS, HEMASUDHA; R, THIRUCHELVI; P, BALASHANMUGAM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The marine seaweed Gracilaria edulis was collected from Rameshwaram Mandapam coast. The main objective of G. edulis was to check about the antioxidant, antibacterial, and anticancer activity. The potential use of seaweeds is to prevent colon cancer and leukemia. The crude extract of antioxidant activity was done in methanol and aqueous extract in various concentrations using DPPH assay. The antibacterial activity was analyzed in methanol extract. The antibacterial activity was tested in Gram-positive bacteria (Staphylococcus aureus) and Gram-negative (Pseudomonas) bacteria with various concentration. The anticancer activity was tested against using the breast cancer cell line (MDA-MB231) Methods: The antibacterial activity was checked by crude methanol extract using Gram-positive bacteria (S. aureus) and Gram-negative bacteria (Pseudomonas) with different concentrations. The antioxidant activity was determined using DPPH radical scavenging assay in various concentrations. The anticancer activity was done using 3-(4, 5- dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay against breast cancer cell line (MDA-MB231). Results: The antioxidant activity of marine red algae was checked using the stable DPPH radical scavenging assay. The antibacterial activity was analyzed and shows the activity of two different bacteria strain against methanol extract. The anticancer activity was done against breast cancer cell line using MTT assay. Conclusion: Thus, the result shows that red algae G. edulis has good biological activity, and further it can be carried out in pharmaceutical, food preservatives, and cosmetic purpose.